(untitled) (World Bulletin of Management and Law, 2022)
The article analyzes the essence and features of the application of the institution of prejudice in criminal proceedings in some countries, examines the opinions of scientists on the procedure for the implementation of prejudice, makes some judgments on the use of prejudice in the provision of legal assistance in international cooperation.